(untitled) (Journal of Economic Research & Business Administration, 2015)
The aim of this paper is to define the theoretical framework of work values and make analysis of today’s Kazakh employees work values. Theoretical framework concentrates on discussing the genesis and evolution of views related to work values around the world and in Kazakhstan. In this study the analysis of today’s Kazakh workers shows that work values of modern Kazakhs has include, the elements of nomadic cultural tradition of Kazakhs; the elements which had been formed directly under the influence of the Soviet system of labor relations, and, finally, elements borrowed from the Western economic culture.